CD16+ Monocyte Subsets Are Increased in Large Abdominal Aortic Aneurysms and Are Differentially Related with Circulating and Cell-Associated Biochemical and Inflammatory Biomarkers. Issue 2 (21st May 2013) - Ghigliotti, Giorgio; Barisione, Chiara; Garibaldi, Silvano; Brunelli, Claudio; Palmieri, Daniela; Spinella, Giovanni; Pane, Bianca; Spallarossa, Paolo; Altieri, Paola; Fabbi, Patrizia; Sambuceti, Gianmario; Palombo, Domenico
Abstract : Proinflammatory components are present in abdominal aortic aneurysm (AAA). Circulating monocytes display heterogeneity, and three subsets have been identified, based on the differential expression for CD14 and CD16 receptors: CD14 + CD16 -, classical, CD14 + CD16 +, intermediate and CD14 dim CD16 +, non-classical monocytes. Increased proinflammatory CD16 + monocytes with high expression of CD143 are present in CKD patients. D-dimer is increased in AAA patients, and might contribute to the pro-inflammatory response associated to circulating monocytes. We aimed to investigate the frequency of CD14 + CD16 +, CD14 dim CD16 + monocytes and monocyte CD143 expression in AAA patients, and their relationship with D-dimer, eGFR and other inflammatory parameters. Blood from 74 AAA patients and 30 healthy controls was analyzed to determine the frequency of CD14 +, CD16 +, CD14 dim CD16 + monocytes and the monocyte CD143 expression by means of flow-cytometry. AAA patients had expanded CD16 + SUPsets (CD14 + CD16 + : 7.66 ± 0.31% vs 5.42 ± 0.27%; CD14 dim CD16 + : 7.43 ± 0.48% vs 5.54 ± 0.38%, AAA vs controls, mean ± SE, both p<0.05). CD14 + CD16 + cells were associated to D-dimer and age, and to reduced eGFR. CD14 dim CD16 + cells were associated to uric acid, surface CD143, and reduced count of total leukocytes and neutrophils. Within AAA patients, the two CD16 + supsets and the monocyte CD143 expression display different relationships with D-dimer, parameters of renal function and circulating biochemical and inflammatory biomarkers.